Pemberdayaan Masyarakat Desa Kloposepuluh melalui Edukasi Literasi Penguatan Ekonomi Digital dan Pembinaan Spiritual untuk Mewujudkan Transformasi Sosial - Mir'atus Sa'diyah; khusnul isma Nuriza; Mohammad Azka Fikri (STAI Senori Tuban, 2026)
The Community Service Program (Kuliah Kerja Nyata/KKN) in Kloposepuluh Village, Sukodono District, Sidoarjo Regency was implemented to address three main issues: low educational literacy among children, limited digital capacity of micro, small, and medium enterprises (MSMEs), and weak social–spiritual community participation. The program aimed to strengthen human resource quality through integrated educational, economic, and spiritual empowerment. This study employed a Participatory Rural Appraisal (PRA) approach, emphasizing active community involvement in problem identification, planning, implementation, and evaluation, with students acting as facilitators. Data were collected through observation, interviews, focus group discussions, and participatory evaluation. The results indicated increased learning motivation and literacy participation among children, improved awareness of self-protection and anti-bullying behaviors, enhanced MSME capacity through QRIS registration, business legality (NIB), and digital marketing adoption, as well as strengthened social–spiritual cohesion through mosque-based activities. Overall, the PRA-based approach effectively encouraged community participation, independence, and sustainable social transformation.